2018
DOI: 10.1080/02699931.2018.1520077
|View full text |Cite
|
Sign up to set email alerts
|

A different kind of pain: affective valence of errors and incongruence

Abstract: People hiss and swear when they make errors, frown and swear again when they encounter conflicting information. Such error- and conflict-related signs of negative affect are found even when there is no time pressure or external reward and the task itself is very simple. Previous studies, however, provide inconsistent evidence regarding the affective consequences of resolved conflicts, that is, conflicts that resulted in correct responses. We tested whether response accuracy in the Eriksen flanker task will mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 24 publications
5
21
2
Order By: Relevance
“…When participants responded correctly, they demonstrated a more positive reaction in incongruent trials compared to congruent ones. This effect was also replicated by Ivanchei and colleagues (Ivanchei et al, 2019).…”
Section: Correct Responses Alleviate the Negative Evaluation Of Conflictsupporting
confidence: 56%
See 2 more Smart Citations
“…When participants responded correctly, they demonstrated a more positive reaction in incongruent trials compared to congruent ones. This effect was also replicated by Ivanchei and colleagues (Ivanchei et al, 2019).…”
Section: Correct Responses Alleviate the Negative Evaluation Of Conflictsupporting
confidence: 56%
“…However, although the effect disappeared over time, it never reversed, as in the studies of Schouppe and colleagues (2015) and Ivanchei and colleagues (2019) where correct responses to incongruent stimuli were found to induce positive affect. Schouppe and colleagues (2015) and Ivanchei and colleagues (2019) also used additional practice with the Stroop task prior to the "Stroop + target evaluation" trials (i.e., 24 trials in Schouppe et al, 2015; and until criterion in Ivanchei et al, 2019). Therefore, observing a more positive evaluation following correct responses to incongruent trials (relative to congruent trials) may necessitate more experience with the conflict task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, behavioral studies using affective priming paradigms have shown that passively viewing a conflicting stimulus (e.g. Stroop) leads to faster detection of negative relative to positive stimuli (Dreisbach & Fischer, 2012), while actively and correctly responding to conflict produced the reversed pattern with faster detection of positive relative to negative stimuli after conflict (Schouppe et al, 2015;Ivanchei et al, 2018). Similarly, while passive viewing of conflict stimuli for short durations led to more negative evaluations, increased viewing time led to more positive evaluations, suggesting that initial negative valence is counteracted by emotion regulation with sufficient time (Fritz & Dreisbach, 2015; see also Pan, Shi, Lu, Wu, Xue, & Li, 2016, Exp.…”
Section: Implicit Affect Regulation Following Controlled Behaviormentioning
confidence: 99%
“…According to the authors of the technique, the subject with a higher readiness to interpret the signals they receive as stressful and dangerous will identify these words faster, which will be reflected in the objective criterion, i.e. shorter recognition time (Ivanchei et al, 2019;Shcherbakova et al, 2018). Plutchik et al (1979) method "Diagnostics of psychological defense typology" adapted to Russian sample (as cited in Fetiskin et al, https://doi.org/10.15405/epsbs.2020.10.04.16 Corresponding Author: Anna Valerevena Emelyanenkova Selection and peer-review under Folkman and Lazarus's (1988) "Coping test" adapted to Russian sample by Kryukova and Kuftyak (2007) were used as subjective methods.…”
Section: Methodsmentioning
confidence: 99%